ANALISIS PENGARUH POTENSI AIR LAUT TERHADAP AIR TANAH KECAMATAN KENJERAN, KOTA SURABAYA - Sari, Avellyn Shinthya; Atiyatussa’adah, Eva (Institut Teknologi Adhi Tama Surabaya, 2025)
Seawater intrusion is the process of seawater entering the aquifer due to the presence of empty pore spaces, which then causes the mixing of seawater with groundwater. The problems in this study are as follows: how is the decrease in groundwater quality and changes in groundwater patterns. The method used is to perform a hydrochemical. Based on the results of the study, the groundwater level is known to range from 5 meters to 6 meters. This position will affect the effectiveness of preventing seawater intrusion towards the land/aquifer. If the interface position is fully closed to a flat/impermeable layer under the iron sand deposits, namely the gravel layer and the siltsone layer, then preventing seawater intrusion will be effective. However, if the interface hangs with a depth that is closer to the seawater surface/local land surface, then seawater infiltration will be wider. This results in the opening of the interface with a width of between 100 (aquifer layer).